STRUCTURAL-CONTENT ASPECT OF THE METHODOLOGICAL COMPONENT OF THE CONTENT OF TEACHING A FOREIGN LANGUAGE IN THE CONDITIONS OF DIGITALIZATION OF EDUCATION - Telman Grigoryan; Tatiana Lomteva (Вестник Северо-Кавказского федерального университета)
The article is devoted to the consideration of the content of teaching a foreign language in the era of digitalization of education. During the period of world integration, informatization and computerization of all spheres of human life, a common cultural space is formed, as a result of which the education system is also subject to change as a sociocultural phenomenon. Learning a foreign language becomes a necessary condition for the normal coexistence of individuals of different ethnic groups. In this process, the methodological component of the content of teaching is an important tool for mastering a foreign language. Similar statement of the problem includes such aspects as the place and the role of the methodological component in a structural basis of content of teaching with further determination of its essence. In this regard, the article studies such aspects of the problem as the state of the modern education system and the process of its digitalization in the context of the informatization of society. The analysis concludes that in these conditions the role and place of the methodological component is determined by the nature of modern society and the tendency towards digitalization in the context of the article - at the level of methods and techniques for mastering a foreign language in communicative presentation.